2012
DOI: 10.1159/000345036
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Area Level Socioeconomic Status and Its Association with Cognitive Function and Cognitive Impairment (Low MMSE) among Community-Dwelling Elderly in Singapore

Abstract: Background/Aims: Neighborhood socioeconomic status (SES) can affect cognitive function. We assessed cognitive function and cognitive impairment among community-dwelling elderly in a multi-ethnic urban low-SES Asian neighborhood and compared them with a higher-SES neighborhood. Methods: The study population involved all residents aged ≥60 years in two housing estates comprising owner-occupied housing (higher SES) and rental flats (low SES) in Singapore in 2012. Cognitive impairment was defined as <24 on the Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 97 publications
8
58
1
1
Order By: Relevance
“…Similar results were observed in population studies of the elderly in Asia (> 60 years) 11 , of British adults and elderly (> 50 years) 13 and of the American elderly (> 65 years) 12 , in which neighborhoods with low income and educational levels, higher unemployment and sources of public assistance were associated with cognitive decline. Similarly, institutionalized elderly people in Britain (> 65 years) living in neighborhoods with a higher deprivation index were twice as likely to experience cognitive decline compared to areas with less deprivation, regardless of individual education or social class 29 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were observed in population studies of the elderly in Asia (> 60 years) 11 , of British adults and elderly (> 50 years) 13 and of the American elderly (> 65 years) 12 , in which neighborhoods with low income and educational levels, higher unemployment and sources of public assistance were associated with cognitive decline. Similarly, institutionalized elderly people in Britain (> 65 years) living in neighborhoods with a higher deprivation index were twice as likely to experience cognitive decline compared to areas with less deprivation, regardless of individual education or social class 29 .…”
Section: Discussionsupporting
confidence: 84%
“…Studies carried out in Asia 11 , North America 12 and Europe 13 have found that elderly people who lived in neighborhoods with worse socioeconomic indicators, such as lower income or education level and higher unemployment, had lower cognitive performance scores regardless of individual socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there seems to be a consensus in the literature about the existence of an inverse relationship between depression and cognitive performance 11,12 . Second of all, the results of the present study corroborate the evidence that better cognitive function is associated with better nutritional status 10 , a higher level of physical activity 9 , a better self-perception of health-related quality of life 3 , a higher level of social satisfaction 29,12 and a higher socioeconomic level 30,13 . Evidence of cognitive decline is associated with very sensitive areas such as memory, executive function, language, gnosis/perception and visual-spatial function, which determine independence, quality of life and the strength of relationships between multiple variables taken into consideration in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, good social and emotional support, including regular social contacts, apart from a good relationship among community members, are factors that increase the protection of cognitive function 12 . Finally, better life conditions, namely the offer of a greater number of activities, better medical care, favorable material conditions, available literature tools and educational systems throughout life are associated with better cognitive function performance 13,14 . Although some studies have identified the factors that most frequently contribute to cognitive function decline, the interactions between cognitive function predictors must be explored more deeply.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that there are significant variations in cognitive function of groups of older people who reside in different neighborhoods. After adjustment for individual level socioeconomic characteristics, residence in socioeconomically advantaged neighborhoods (with high levels of household income, education and employment) was associated with higher cognitive function, and vice versa [11][12][13][14][15][16][17][18][19][20][21][22][23][24] . However, there were few studies that investigated the physical and social "elder-friendliness" of the built or social environment in the neighborhood, in terms of "walkability" [25] .…”
Section: Introductionmentioning
confidence: 99%